What Factors are Associated with a Second Opioid Prescription after Treatment of Distal Radius Fractures with a Volar Locking Plate?. (December 2015) - Teunis, Teun; Stoop, Nicky; Park, Christine J.; Ring, David
Purpose: Knowledge of factors associated with patient's requests for a second opioid prescription after volar plate fixation of a fracture of the distal radius might inform better pain management protocols and encourage decreased and safer use of opioids. This study tested the primary null hypothesis that there is no difference in demographics, prior opioid prescriptions, injury characteristics, and psychological factors between patients that do and do not receive a second opioid prescription following treatment volar locking plate after distal radius fracture. Patients and Methods: We used data on 206 patients enrolled in one of two prospective studies. Their mean age was 53 years±SD 15, and 60 (30 %) were men. Forty-seven (23 %) patients received a second opioid prescription. We recorded additional demographics, AO fracture type, American Society for Anesthesiologists (ASA) classification, radiographic parameters at the time of injury prior to reduction and after surgery, and catastrophic thinking. Results: Male sex (odds ratio [OR] 2.2, 95 % confidence interval [CI] 1.0–4.6, partial pseudo R 2 =0.018, p =0.044) and greater dorsal angulation of the articular surface on the lateral post injury radiograph (OR 0.98, 95 % CI 0.96 to 1.0, partial pseudo R 2 =0.033, p =0.040) were associated with a second opioid prescription after surgery (pseudo R 2 0.12, p =0.0071). Conclusions One measure of fracture severity (dorsal displacement) was independently associated with a second opioid prescription, but alone it accounted for 3.3 % of the variation. Other factors such as the patient's expectation prior to surgery, in particular the realization that injury and surgery hurt, might be addressed in future research. Level of Evidence: Prognostic II